Analisis Konseptual Tutorial SIPRES Manajemen Platform UPI dalam Mengintegrasikan Ilmu Pengetahuan dan Nilai Tauhid: A Conceptual Analysis of the SIPRES Tutorial UPI Platform Management in Integrating Science and Tawhid Values - Diana Sojiyah Budiwati; Raffa Shara Desfira; Nabila Az-zahra Sholihah; Edi Suresman (Litera Academica Publishing, 2026)
This study aims to conceptually analyze the management of the SIPRES Tutorial UPI Platform in supporting the integration of science and tawhid values in Islamic Religious Education learning in higher education. A non-empirical qualitative approach with a library research method was employed using relevant academic references. The findings indicate that the SIPRES Platform supports digital learning management through POAC management functions (planning, organizing, actuating, and controlling), including attendance management, assignments, student activity monitoring, and spiritual development. The platform facilitates the systematic integration of science, technology, and tawhid values. The study concludes that SIPRES functions not only as a digital learning medium but also as a managerial instrument that strengthens Islamic values in higher education.